2016
DOI: 10.1002/anie.201510611
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Receptors for the High‐Affinity Recognition of O‐GlcNAc Derivatives

Abstract: The combination of a pyrenyl tetraamine with an isophthaloyl spacer has led to two new water‐soluble carbohydrate receptors (“synthetic lectins”). Both systems show outstanding affinities for derivatives of N‐acetylglucosamine (GlcNAc) in aqueous solution. One receptor binds the methyl glycoside GlcNAc‐β‐OMe with K a≈20 000 m −1, whereas the other one binds an O‐GlcNAcylated peptide with K a≈70 000 m −1. These values substantially exceed those usually measured for GlcNAc‐binding lectins. Slow exchange on the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 34 publications
(8 reference statements)
4
88
0
Order By: Relevance
“…Such an analysis can indeed be informative, as it has been often reported that carbohydrate binding in water with inflexible cages is driven substantially by entropy. [17,18] For the specific case of amino saccharides with CB [7], our earlier experiment [25] suggested that entropy participated importantly (ÀTDS/DG % 35 %) in the binding of GalN and GluN, for which the anomer discrimination is more dramatic than for ManN. This substantial entropic contribution is also consistent with recent experimental binding data for polysaccharides with synthetic lectins, [18] for which it was reported that entropy sometimes contributed more to the binding than enthalpy.…”
Section: Decomposition Of Binding Free Energiessupporting
confidence: 82%
“…Such an analysis can indeed be informative, as it has been often reported that carbohydrate binding in water with inflexible cages is driven substantially by entropy. [17,18] For the specific case of amino saccharides with CB [7], our earlier experiment [25] suggested that entropy participated importantly (ÀTDS/DG % 35 %) in the binding of GalN and GluN, for which the anomer discrimination is more dramatic than for ManN. This substantial entropic contribution is also consistent with recent experimental binding data for polysaccharides with synthetic lectins, [18] for which it was reported that entropy sometimes contributed more to the binding than enthalpy.…”
Section: Decomposition Of Binding Free Energiessupporting
confidence: 82%
“…[7] Synthesis 2,4,:T oam ixture of Pd(OAc) 2 (90 mg, 0.40 mmol) and SPhos (330 mg, 0.80 mmol) in toluene (200 mL) were added K 3 PO 4 (13 g, 80 mmol), 4-methoxybenzeneboronic acid (5,9 .1 g, 60 mmol), and 2-bromo-1,3,5-triisopropylbenzene (11g,4 0mmol 1, 147.7, 146.9, 136.7, 132.9, 130.7, 120.5, 113.3, 55.2, 34.2, 30.2, 24.2, 24 (7):B Br 3 (19 g, 77 mmol) was added to as olution of 6 (12 g, 39 mmol) in CH 2 Cl 2 (75 mL) at À80 8C. ESI-HRMS analyses were carried out on aJ EOL JMS-T100LC mass spectrometer by using MeOH solutions of the analytes.…”
Section: Methodsmentioning
confidence: 99%
“…[39] The chemistry of saccharides and related molecules is involved in the metabolic pathways of living organisms. Due to the high number of hydroxyl groups in their structure, saccharides have high solvation enthalpies, [43,44] and are also hard to distinguish from an aqueous solvent. An obvious example is monitoring of blood glucose levels, which is of paramount importance because the breakdown of glucose transport has been correlated with diseases such as diabetes, cystic fibrosis, and cancer.…”
Section: Detection Of Saccharidesmentioning
confidence: 99%